Change in mineral composition and cooking quality in legumes grown on semi-arid alfisols due to elevated CO2 and temperature - K. Sreedevi Shankar; M. Vanaja; Mekala Shankar; Asma Siddiqua; K. L. Sharma; V. Girijaveni; V. K. Singh (Frontiers in Nutrition, 2025)
This study aimed to determine the effects of elevated carbon dioxide (eCO2) and temperature (eT) on the phytochemical and nutritional parameters of legumes. Field experiments were conducted using black gram (Vigna mungo L.), green gram (Vigna radiate L.), and pigeonpea (Cajanus cajan L.) genotypes under the Free Air Temperature Elevation (FATE) facility, with three treatments (Ac, eT, and eCO2 + eT) at ICAR-CRIDA, Hyderabad. The results revealed that the negative impact on both phytochemical and nutritional quality was greater under eT compared to eCO2 + eT. Specifically, protein content decreased by 25.6% under eT + eCO2, while the ash content increased by 38.19%. Carbohydrate levels also decreased by 5.53% under these conditions. The reduction in micronutrients (Zn, Fe, Mn, and Cu) was more pronounced than in macronutrients (P, Ca, and Mg) across the three crops. Moreover, principal component analysis (PCA) revealed that the major contributors to PC1 were Mg, crude fiber, cooking time, phosphorus, hydration capacity, ash content, and Mn. The primary contributors to PC2 included swelling capacity, Cu, Mn, carbohydrate, hydration capacity, and Zn. In contrast, the major contributors to PC3 were Ca, Fe, Zn, protein, carbohydrate, swelling index, and ash content. The eigenvalues of principal components, calibrated through different parameters, ranged from 1.052 to 4.755 in black gram and from 1.073 to 6.267 in green gram. This study provides insights into nutritional quality under changing global climate conditions.